Guide to undertaking person-centred inpatient (ward) outpatient (clinic) and dispensary-based pharmacy consultations - Barnett, Nina L (Eur J Hosp Pharm, 2020)
WHO uses the internationally accepted term ‘person-centred care’, also usedby the Royal Pharmaceutical Society in the UK, to highlight the importance of considering that patients are people first; they have families, communities and are living with conditions for which they receive healthcare. The challenge that faces pharmacy professionals is embedding a person-centred approach to pharmacy practice. In a hospital setting, there are specific processes that must be completed to optimise safe, efficient and effective practice, however thesetend to be professionally focused. The coaching model, GROW, supports more person-centred conversations and has been used successfully in health in the National Health Service (NHS) in the UK . Inin pharmacy, practitioners were challenged with the task of integratingperson-centred consultation techniques as part of the pharmacy processes they were required to complete within their everyday activities. Therefore, a set of person-centred questions were developed, using concepts from GROW and the Four E’s, to create guides for practitioners to use within each of the pharmacy processes they commonly undertook. The guides were piloted with three pre-registration pharmacists and, following modification, were included in the skill development sessions described in a related publication in this issue ’A pilot study to evaluate knowledge of person-centred care (PCC), before and after a skill development programme, in a cohort of pre-registration pharmacists (PRPs) within a large London Hospital’. These guides are used by pharmacy staff in the author’s organisation to support a person-centred approach to pharmacy practice.